Innovation of Higher Education. - Cho, Tong-sŏng (Seoul Selection, 2020)
Incheon National University (INU) blazes the trail of innovationINU spearheads change in academia in Korea and abroadThis book outlines case studies of innovation at INU, which developed a new paradigm of innovation driven by field staff. The text itself is the product of hands-on fieldwork carried out by 275 members of the INU staff. These staff members demonstrate how the driving force for innovation rises from the change-makers themselves. The book shares INU's tried and tested lessons on problem-solving, implementing innovation, surveying public opinion, and gathering feedback from the fie.